2022
DOI: 10.1128/spectrum.02265-21
|View full text |Cite
|
Sign up to set email alerts
|

Avian Hepatitis E Virus ORF2 Protein Interacts with Rap1b to Induce Cytoskeleton Rearrangement That Facilitates Virus Internalization

Abstract: Rap1b is a multifunctional protein that is responsible for cell adhesion, growth, and differentiation. The inactive form of Rap1b is phosphorylated and distributed in the cytoplasm, while active Rap1b is prenylated and loaded with GTP to the cell membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…It is observed that avian HEV upregulates and activates Rap1 during infection and consequently rearranges the cytoskeleton to promote virus internalization by permissive cells. 49 Our data show that 25HC decreased active Rho GTPases and Rap1 levels in cervical epithelial cells, most likely through its restriction of isoprenoid synthesis (Figure 5D and 6). Our findings support that small GTPase prenylation could be a promising target for HPV infection.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is observed that avian HEV upregulates and activates Rap1 during infection and consequently rearranges the cytoskeleton to promote virus internalization by permissive cells. 49 Our data show that 25HC decreased active Rho GTPases and Rap1 levels in cervical epithelial cells, most likely through its restriction of isoprenoid synthesis (Figure 5D and 6). Our findings support that small GTPase prenylation could be a promising target for HPV infection.…”
Section: Discussionmentioning
confidence: 63%
“…The mechanism of this actin coordination efficacy is correlated with the LIMK/cofilin pathway. It is observed that avian HEV upregulates and activates Rap1 during infection and consequently rearranges the cytoskeleton to promote virus internalization by permissive cells 49 . Our data show that 25HC decreased active Rho GTPases and Rap1 levels in cervical epithelial cells, most likely through its restriction of isoprenoid synthesis (Figure 5D and 6).…”
Section: Discussionmentioning
confidence: 66%
“…The mechanism of this actin coordination efficacy is correlated with the LIMK/cofilin pathway. It is observed that avian HEV upregulates and activates Rap1 during infection and consequently rearranges the cytoskeleton to promote virus internalization by permissive cells (46). Our data show that 25HC decreased active Rho GTPases and Rap1 levels in cervical epithelial cells, most likely through its restriction of isoprenoid synthesis(Figure 5D, Figure 6) .…”
Section: Discussionmentioning
confidence: 65%
“…Uncontrolled Rap1b activation is often associated with the occurrence of tumors, especially highly metastatic malignant ones [ 23 ], in which the process of Rap1b-induced regulation of the cytoskeleton is significant [ 24 ]. Nevertheless, cytoskeleton rearrangement occurs during early HSV-1 viral entry, intracellular trafficking, and release and can be hijacked by the viruses to facilitate viral replications such as those of porcine hemagglutinating encephalomyelitis virus (PHEV) [ 25 ], hepatitis E virus (HEV) [ 26 ], and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 27 , 28 , 29 ]. However, the impact of Rap1b in regulating cell membranes during viral replication has rarely been assessed aside from its role in the proliferation and migration of hepatitis-B-infected hepatocytes [ 30 ].…”
Section: Introductionmentioning
confidence: 99%